Untroubling abortion: A discourse analysis of women’s accounts - Beynon-Jones, Siân M (Feminism & psychology, 2017)
In this paper, I highlight key differences between a discourse analytic approach to women’s accounts of abortion and that taken by the growing body of research that seeks to explore and measure women’s experiences of abortion stigma. Drawing on critical analyses of the conceptualisation of stigma in other fields of healthcare, I suggest that research on abortion stigma often risks reifying it by failing to consider how identities are continually re-negotiated through language-use. In contrast, by attending to language as a form of social action, discursive psychology makes it possible to emphasise speakers’ capacity to construct “untroubled” (i.e. non-stigmatised) identities, while acknowledging that this process is constrained by the contexts in which talk takes place. My analysis applies these insights to interviews with women concerning their experiences of having an abortion in England. I highlight three forms of discursive work through which women navigate “trouble” in their accounts of abortion, and critically consider the resources available for meaning-making within this particular context of talk. In doing so, I aim to provoke reflection about the discursive frameworks through which women’s accounts of abortion are solicited and explored.